The Influence of Internal Communication and Leadership Style on the Work Motivation of Specialists in Public Relations Agency XYZ - Girzavania Nugrita Nugroho; Ratri Wahyuningtyas (International Forum of Researchers and Lecturers, 2025)
This study examines the influence of internal communication and leadership style on employee work motivation at Public Relation Agency XYZ. The research focuses on understanding how these two organizational factors shape the motivation levels of employees, particularly freelance experts who contribute significantly to the agency’s performance and service quality. Using a quantitative approach, data were collected through a structured survey designed to capture employees’ perceptions of communication effectiveness, leadership characteristics, and motivational conditions within the agency. The collected data were then analyzed using SmartPLS to test the proposed relationships. The findings indicate that both internal communication and leadership style exert a significant and positive influence on work motivation, highlighting the crucial role of clear information flow and supportive leadership behavior. Moreover, the results suggest that enhancing communication practices and applying a more transformational leadership style can substantially improve employee motivation. This study offers practical recommendations for strengthening internal communication systems and leadership development initiatives to foster higher engagement, productivity, and overall motivation among employees at Public Relation Agency XYZ.